Pengaruh Perbedaan Intensitas Latihan Atlet Sepeda Terhadap Berat Badan dan Body Water (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
This research intended to determine the influence of various exercise intensities to hydration status in cyclists based on body weight and body water alteration. This research was done by measured body weight and body water before and after exercise in various intensities. The data measured during April-June 2015 with nine cyclists of Pegasus Continental Cycling Team located in Yogyakarta. Sampling technique used total sampling. Based on One-Way ANOVA statistical analysis, showed significant differences between body weight alteration before and after exercise in light intensity, moderate intensity, and strong intensity. The result proofed by p-value 0,000<0,05. However, there are no significant differences between body water alteration in average intensity and strong intensity. From the result, we can conclude that in various exercise intensities, light, moderate, and high influence athletes hydration status based on body weight and body water alteration before and after exercise. But, body water change in average intensity and vigorous energy are not different. Whereas, body weight change in light intensity is different from the average intensity and strong intensity.